+0  
 
0
106
2
avatar

4p- 6p = 0

Guest Mar 27, 2017
Sort: 

2+0 Answers

 #1
avatar
0

p=0 or p=1.5

Guest Mar 27, 2017
 #2
avatar+4155 
+2

Guest got the right answers but here's an explanation:

4p2 - 6p = 0

 

Factor out a p from both terms.

(p)(4p - 6) = 0

 

Set each factor equal to zero.

(If either one was zero, then the whole thing equals zero.)

Either        p = 0          or       4p - 6 = 0

                                                     p = 6/4 = 1.5

hectictar  Mar 27, 2017

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details